«COGNITIVE HUMAN» IN INNOVATIVE DEVELOPMENT OF ECONOMY: TO THE PROBLEM OF ESSENCE AND REPRODUCTION OF ITS CAPITAL - Igor Gruzkov; Vladimir Gruzkov (Вестник Северо-Кавказского федерального университета, 2022)
Cognitive direction in the economy is growing since the beginning of 1950-ies. However, idea and practice model, «cognitive man», in Russian economic science is in the development stage. Today the problem isn t reflected in Internet search engines. All together, it gives rise to the common assumption: introduction of a cognitive context into economic science, makes it a new content, study of which requires integration of efforts of representatives of different scientific disciplines concerning man and society. The article presents the author's model of «cognitive man» attempts to formulate ideas about its nature, place and role in the formation of the prerequisites of the knowledge economy, conditions, characteristics and trends of reproduction of its capital.